2020
DOI: 10.2147/ijn.s210320
|View full text |Cite
|
Sign up to set email alerts
|

<p>Nano Encapsulated Curcumin: And Its Potential for Biomedical Applications</p>

Abstract: Curcumin, a yellow-colored polyphenol extracted from the rhizome of turmeric root, is commonly used as a spice and nutritional supplement. It exhibits many pharmacological activities such as anti-inflammatory, anti-bacterial, anti-cancer, anti-Alzheimer, and anti-fungal. However, the therapeutic application of curcumin is limited by its extremely low solubility in aqueous buffer, instability in body fluids, and rapid metabolism. Nano delivery system has shown excellent potential to improve the solubility, bioc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
85
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(87 citation statements)
references
References 185 publications
(189 reference statements)
1
85
0
1
Order By: Relevance
“…Table 2 summarizes the commercially approved target delivery systems and their active natural products. Improve health life quality, anti-inflammatory effect in patients with solid tumors [701] ALL = acute lymphoblastic leukemia.…”
Section: Boswellic Acids Clinical Studiesmentioning
confidence: 99%
“…Table 2 summarizes the commercially approved target delivery systems and their active natural products. Improve health life quality, anti-inflammatory effect in patients with solid tumors [701] ALL = acute lymphoblastic leukemia.…”
Section: Boswellic Acids Clinical Studiesmentioning
confidence: 99%
“…With the researches of Curcumin nanoformulations may address the limitation of low bioavailability and provides a promising therapeutic strategy, there is the potential of Curcumin being a therapeutic agent to suppress renal fibrosis and delay the development of DN. 26 Previously, we have reported that Curcumin plays an important role in cellular antioxidant defense via the activation of Nrf2 and HO-1, thereby protecting HG-induced EMT in the NRK-52E cells. 27 However, whether Curcumin has anti-fibrosis effects in DKD, especially in TLR4-NF-κB during EMT of kidney tubular epithelial cell is still unknown.…”
Section: Introductionmentioning
confidence: 97%
“…For centuries, crude curcumin, a traditional Asian medicine, was used as a food spice and dietary supplement [ 3 , 4 ]. Curcumin or its family, curcuminoids, exhibits many potential benefits and pharmacological activities such as anti-cancer, anti-Alzheimer, antifungal, antibacterial, antioxidant, and anti-inflammatory agents [ 5 , 6 , 7 ]. Curcumin is Generally Recognized as Safe (GRAS) by the FDA, which strengthens its case as a potential natural drug [ 8 ].…”
Section: Introductionmentioning
confidence: 99%